Functional data analysis of lower-limb joint kinematics during badminton lunges under fatigue - Fang, Yuling; Zhang, Xingchen; Sun, Yang; Wu, Hanbing; Pei, Huanran; Gao, Jingwen; Liu, Jiujiang; Zhu, Qing; Gao, Yuan (Frontiers in Bioengineering and Biotechnology, 2026)
ObjectiveThis study applied Functional Data Analysis (FDA) to investigate the effects of fatigue on lower-limb joint kinematics during badminton lunges.MethodsSeventeen elite male badminton players executed both forward and 45° sideways forehand lunges before and after a fatigue protocol. Three-dimensional kinematic data of the lower limbs were collected using a motion capture system synchronized with force plates. Functional principal component analysis (FPCA) was employed to reduce dimensionality and extract key features from the time-series curves of hip, knee, and ankle joint angles. Paired-samples t-tests were used to compare the principal component scores before and after the induction of fatigue.ResultsFatigue significantly altered lower-limb movement patterns. Sagittal-plane analyses revealed a decreased range of motion in hip and knee flexion, contrasted with an increased range of ankle dorsiflexion (p < 0.05). In the coronal plane, hip and knee abduction-adduction ranges decreased, while ankle inversion-eversion ranges increased (p < 0.05).ConclusionFatigue triggered a “top-down” compensatory response: proximal joints stiffened to stabilize, while the ankle enhanced flexibility to compensate. This “proximal-stiffening, distal-mobility” pattern maintained performance but may have redistributed loads, potentially raising the risk of ACL and lateral ankle ligament injuries. These findings help guide fatigue-specific training and injury-prevention strategies.